The effects of prochloraz on the growth and yield of oilseed rape - Stafford, Judith Anne (1996)
Yield production was investigated in the winter oilseed rape variety Capricorn by comparing crops grown under standard husbandry conditions in three seasons (1991, 1992 and 1993 harvest years). Also investigated were the effects of the phytotonic imidazole fungicide prochloraz on the physiology of yield production. Prochloraz was applied in autumn, spring and summer in all possible combinations (eight treatments), except in the second season (1992), when the autumn application was omitted. Crop growth and development were studied in detail using stratified sampling in 20 cm layers. Detailed growth analysis between flowering and final harvest was restricted to untreated controls and plots receiving all three prochloraz applications. Solar radiation interception was measured using tube solarimeters arranged to correspond with layers of the profile obtained in sampling.